From Mother's Ruin to Ginaissance: Emergence, settlement and resettlement of the gin category. Issue 7 (July 2020) - Pedeliento, Giuseppe; Andreini, Daniela; Dalli, Daniele
This article provides a historically grounded explanation of category emergence and change by using the gin category as an example. Formerly a standardized spirit produced by a narrow group of large England-based producers, gin has become a premium craft spirit made by thousands of big and small producers in every corner of the world – a categorical shift that commentators have dubbed the 'ginaissance'. We approach product categories as socially constructed entities and make informed use of history to explain the successive categorical dynamics. Strategic action field theory is applied to explain how internal and external category actors interact to create and change product meanings and affect categorical configurations. Our results show how the intricate, complex and historically embedded processes that the product category underwent first triggered stigmatization and then put conditions in place that led to concentration and made the current ginaissance possible. Findings drawn from this study of gin contribute to research on product categories by revealing some peculiar dynamics of concentration and partitioning, status recategorization and categorical stigma, which are summarized in an empirically grounded process model of category emergence and change.